PENGARUH BRAND AWARENESS DAN BRAND TRUST TERHADAP NIAT BELI KONSUMEN BATICUE - Chyntia Christina Suciawan; Tina Melinda (Universitas Ciputra Surabaya, 2022)
Fashion development in Indonesia recently develope rapidly. This thing is evidenced by the number of local fashion business that has different value ​​and brand identity. One of the local fashion brands that has unique brand value and identity is baticue. Baticue is fashion business that gives batik nuance in each product. At this time, brand awareness and brand trust are the keys of business success because consumers trust the business so that can increase one's purchase intention. This research is done to find out how important brand awareness and brand trust on purchase intention of baticue consumers is. To get data, therefore the writer distributes questionnaires to 97 respondents that have age criteria of 17 to 26 years old, follow trend development and interested towards product that has batik nuance. In this research, using non-probability sampling method with purposive sampling type that is used for sampling. Data that is obtained will be analyzed using SmartPLS (Partial Least Square) program. The data that is used consists of two, that is, primary data and secondary. Primary data consists of questionnaire result, whereas secondary data from this research is from journal and some other things that are related to research variable. The result of this research proves that brand awareness and brand trust affect positive on purchase intention of Baticue consumers.